What the Face RevealsBasic and Applied Studies of Spontaneous Expression Using the Facial Action Coding System (FACS) 2005
DOI: 10.1093/acprof:oso/9780195179644.003.0021
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Experience and Expression in Schizophrenia and Depression

Abstract: The emotional responses of schizophrenic, depressed, and normal subjects and whether differences in the emotional responding of these groups depended on how emotional responses were elicited or measured were examined. Twenty-three blunted and 20 nonblunted schizophrenics, 17 unipolar depressed subjects, and 20 normal subjects were exposed to a series of affect-eliciting stimuli. The stimuli varied in valence (positive vs. negative) and in level of cognitive demand. Subjects reported their subjective experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
65
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 8 publications
(8 reference statements)
13
65
0
Order By: Relevance
“…Second, we hypothesize that a cool emotional style is part of a larger pattern of disengagement from emotion, people, and goals. Such disengagement could contribute to anhedonia, diminished emotional reactivity, and affective flattening, all of which are associated with MDD (e.g., Berenbaum and Oltmanns 1992;Bylsma et al 2008). This is consistent with research by Gohm (2003) who found that emotionally cool individuals are least reactive to mood manipulations.…”
Section: Discussionsupporting
confidence: 81%
“…Second, we hypothesize that a cool emotional style is part of a larger pattern of disengagement from emotion, people, and goals. Such disengagement could contribute to anhedonia, diminished emotional reactivity, and affective flattening, all of which are associated with MDD (e.g., Berenbaum and Oltmanns 1992;Bylsma et al 2008). This is consistent with research by Gohm (2003) who found that emotionally cool individuals are least reactive to mood manipulations.…”
Section: Discussionsupporting
confidence: 81%
“…Most of the studies observed higher levels of anhedonia in patients with schizophrenia, specifically for social rather than physical experiences [19][20] , compared to healthy subjects [21][22][23][24][25][26][27] . Furthermore, literature agrees that 'wanting', more than 'liking', is impaired in Schizophrenia 28-31 even in the early phases of the disorder 32 .…”
Section: Introductionmentioning
confidence: 99%
“…As noted previously, Rude et al found an increase in negative emotion words for dysphoric students compared to non-dysphoric students when writing about a their experiences transitioning to college. However, there is a growing literature indicating that depressed mood may be best characterized by a deficit in positivity (Berenbaum & Oltmanns, 1992;Deldin et al, 2001;Sloan, Strauss, & Wisner, 2001;Watson, Clark, Weber, & Assenheimer, 1995). In view of this literature, it was anticipated that dysphoric participants would use fewer positive emotion words in the positive writing condition compared to non-dysphoric participants, while no group differences were expected for negative emotion word use.…”
mentioning
confidence: 99%